First records of Utricularia tenuissima Tutin and U. nigrescens Sylvén (Lentibulariaceae) in north-eastern Brazil - da Silva, Caio Vinicius; da Cruz, Denise Dias (Revista Brasileira de Biociências, 2015)
In Brazil, there are records of Utricularia tenuissima Tutin and U. nigrescens Sylvén from some states in the north, southeast, west-center and south. This work reveals the first records of these two species in the northeast region of Brazil. These species were found on the Reserva Biológica Guaribas, a protected remnant of Atlantic Forest in Paraíba state, and also in a particular area of sugar cane crop at the limit of the Reserve. The habitats are characterized by wetlands, surrounded by natural springs and partially shaded by herbaceous vegetation. In addition to this expansion in the distribution of these species, there are also differences in their morphometric measurements when compared with the measurements presented in the principal work for description of both species.